The aesthetic parameters and their perception in the smile analysis - Mamani Cahuata, Luz (2018)
In the current era; of the cult to the body, to the health, to the image and to the wellbeing; one must have a vision of the patient in a more holistic way; in which, it is not only essential to consider the health and function of the teeth; but seek to achieve the greatest aesthetics of the smile considering the needs and expectations of patients. Therefore, in the present review we aim to know the perception of the aesthetic parameters that are most evaluated in the smile analysis; both by professionals, as by patients.